Effects of harmonics and voltage flickers on a power system in Samutprakarn province, Thailand - Damrong Kamolpattananan; Surapong Chiraratananon; Yu, Cun Yi; Dhadbanjan, Thukaram; Electricity Generating Authority of Thailand (Bangkok : Asian Institute of Technology, 1999)
In recent years, power quality becomes more critical because of the increase in the number of loads sensitive to power disturbances, and as the loads themselves have become major causes of the degradation of power quality. Therefore, power quality responsibility lies with three main groups: the utility company, the customer group, and the manufacturing group. A number of load types used in industries cause harmonic current and voltage fluctuation such as electric arc furnaces (EAFs) that are found in Steel Manufacturing Facility. Due to the arc furnace load, the significant voltage distortion will occur in power system, which effects the other customer in the same area. In the utility side, the system configuration also causes voltage distortion too. Simulation results from HI_ WA VE program show that the fifth harmonic resonance occurs in power system and by changing the configuration of capacitor bank at distribution feeders can solve this problem. Electric arc furnaces cause voltage fluctuation on account of the oscillated of reactive power. The field measurements illustrate the effect of this voltage fluctuation on another customers in the same distribution area. Consequencely, by adding the static VAR compensator at the steel manufacturing can reduced the flicker problem, which can be seen by the simulation results of EMTDC program.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering. School of Environment Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1999
Keywords: Electric power transmission